A Descriptive Research on Learning Difficulties Encountered by PPAPK Students of The English Language Program - Deva Tari Ananda Putri; Sudarsono; Wardah (CV. Eureka Murakabi Abadi, 2022)
This study aims to find out the difficulties in learning PPAPK 2017/2018 of English students. The analysis focused on the analysis of difficulties based on interviews and questionnaires. The researcher used the descriptive quantitative technique to evaluate ordinal data to determine the percentage of students who had learning difficulties. There are 30 participants in this research. The results showed that learning difficulties received a high percentage. The questionnaire fields included reading, spelling and writing, math and logic, emotion and self-control, listening, and attention. The researcher got the data from the questionnaire that had been distributed. One of the most prominent suggestions made in this study is to focus on the need to diversify teaching methods, reduce the teaching burden for teachers from lessons, and open channels of communication between family and university to follow up on students'' affairs